An Analysis of Classroom Management in Social Science Learning to Strengthen Character Education in Class V at SD Negeri Kandangan 1 Sleman Yogyakarta - Wijayanti, Dwi; Kusuma , Anggi Yudha; Sari, Dyan Indah Purnama; Pratomo, Wachid (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to, (1) describe the class management process in social studies learning to strengthen social care character education, (2) describe the class management process in social studies learning to strengthen responsible character education, (3) describe the supporting and inhibiting factors in classroom management in social studies learning to strengthen character education, (4) describe solutions to classroom management obstacles in social studies learning to strengthen character education. This research is descriptive qualitative research. The research sample was determined using purposive sampling. The data collection process uses observation, interview and documentation techniques. Data validity techniques use data triangulation which includes source triangulation, technique triangulation, and time triangulation. This research consists of four steps of data analysis: data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that (1) teachers carry out classroom management in social studies learning to strengthen social care character education. The teacher forms students into several groups then looks for community activities around their neighborhood, and also makes donations if there are people affected by natural disasters. (2) To strengthen the character of responsibility, teachers give students individual assignments with time limits, and students carry out class pickets according to their respective schedules. (3) Supporting factors for classroom management in social studies learning to strengthen character education are good communication between teachers and parents, social studies material that is relevant to everyday life, students who are active in discussions and teachers who use technology. Inhibiting factors include the large number of students and not all students being easy to manage. (4) Solutions to these obstacles include schools creating additional tutoring programs, singing national songs or regional songs before learning, and carrying out 3S habits (senyum, sapa, salam/ smile, say hello, greet).